Spontaneous formation of β-sheet nano-barrels during the early aggregation of Alzheimer's amyloid beta. (June 2021) - Sun, Yunxiang; Kakinen, Aleksandr; Wan, Xulin; Moriarty, Niamh; Hunt, Cameron P.J.; Li, Yuhuan; Andrikopoulos, Nicholas; Nandakumar, Aparna; Davis, Thomas P.; Parish, Clare L.; Song, Yang; Ke, Pu Chun; et al.
Highlights: Soluble low-molecular-weight oligomers have been hypothesized as causative to neurodegeneration in Alzheimer's disease. The oligomers are challenging to characterize due to their polymorphic, heterogeneous and transient nature. We performed the first synergic validation of the structure, dynamics and toxicity of full-length Aβ42 oligomers. Aβ oligomers assumed nanosized β-barrels and impaired the cognitive function in a mouse model. The occurrence of β-barrels supports their roles as the common toxic intermediates in Alzheimer's and a therapeutic target. Graphical Abstract: Free-energy landscape of Aβ peptides in aggregation. Aβ monomers initially assemble into low β-sheet content oligomers, followed by conformational conversion into high β-sheet abundant oligomers (including β-barrels). Eventually, the β-sheet rich oligomers are converted into proto-fibrils by crossing a high free-energy barrier. ga1 Abstract: Soluble low-molecular-weight oligomers formed during the early aggregation of amyloid peptides have been hypothesized as a major toxic species of amyloidogenesis. Herein, we performed the first synergic in silico, in vitro and in vivo validations of the structure, dynamics and toxicity of Aβ42 oligomers. Aβ peptides readily assembled into β-rich oligomers comprised of extended β-hairpins and β-strands. Nanosized β-barrels were observed with certainty with simulations, transmission electron microscopy and Fourier transform infrared spectroscopy, corroborated by immunohistochemistry, cell viability, apoptosis, inflammation, autophagy and animal behavior assays. Secondary and tertiary structural properties of these oligomers, such as the sequence regions with high β-sheet propensities and inter-residue contact frequency patterns, were similar to the properties known for Aβ fibrils. The unambiguous spontaneous formation of β-barrels in the early aggregation of Aβ42 supports their roles as the common toxic intermediates in Alzheimer's pathobiology and a target for Alzheimer's therapeutics.